2011
DOI: 10.1177/1087057111424605
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Selective Class II Histone Deacetylase Inhibitors Using a Novel Dual-Parameter Binding Assay Based on Fluorescence Anisotropy and Lifetime

Abstract: IntroductIon The family of histone deacetylases (hdacs) has emerged as an important novel class of targets for pharmaceutical intervention on different types of cancer.1 there are 11 zinc-dependent hdacs subdivided in classes i, iia, iib, and iV and 7 hdacs that depend on nad + , the so-called sirtuins. hdacs and their antagonistic opponents, histone acetyl transferases (hats), regulate a variety of genes and cellular functions through balancing the acetylation status of histones and many nonhistone proteins.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
9
0
2
Order By: Relevance
“…For this study, we used N ‐lauroyl‐( l )‐phenylalanine, a recently identified class IIa specific histone deacetylase inhibitor (HDI; ref. 30). The deacetylase activity associated with immunoprecipitated HDAC4, but not with immunoprecipitated HDAC3, was inhibited by the HDI (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this study, we used N ‐lauroyl‐( l )‐phenylalanine, a recently identified class IIa specific histone deacetylase inhibitor (HDI; ref. 30). The deacetylase activity associated with immunoprecipitated HDAC4, but not with immunoprecipitated HDAC3, was inhibited by the HDI (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the prosurvival role of class IIa HDACs could have a therapeutic perspective. A class IIa HDAC inhibitor (30) elicited an antiproliferative response and apoptosis only in MCF7 and ZR‐75‐1 ER + cells. This response was coupled to the up‐regulation of several MEF2 target genes, with Nur77 the more reactive.…”
Section: Discussionmentioning
confidence: 99%
“…19 Introduced in 1970s and with the first dedicated instruments in 1980s, FA has become a standard way of quantitatively measuring biomarkers (first clinical utility of FA), elucidating the mechanism of drug action, and screening potential drug candidates. 20, 21 In the last decade, a variety of FA designs and formats have been utilized to study enzymes, 2224 as well as protein-protein 25 and protein-DNA interactions, with the goal of developing drugs. 2627 A number of recent reviews cover different aspects of these applications in great detail.…”
Section: Introduction: Screening Methods In Drug Discoverymentioning
confidence: 99%
“…-N-lauroyl-(l)-phenylalanine is a class IIa HDACi active in the lM range (Fig. 3) [81]. It was identified during a screening of a commercial available library of compounds.…”
Section: Class Iia Inhibitorsmentioning
confidence: 99%
“…It was identified during a screening of a commercial available library of compounds. The specificity was scored not merely by classical measurements of HDAC activity but also through a fluorescence assay, which exploits the competition between a fluorescent substrate and the putative inhibitor for each purified HDAC [81]. This molecule shows anti-tumoral properties against ER?…”
Section: Class Iia Inhibitorsmentioning
confidence: 99%